A method for preparing extraction residue-based porous carbon electrode material

By performing high-temperature carbonization and activation treatment on the bark of Eucommia ulmoide, combined with the modification technology of graphene oxide and enhancement modifier, the enhanced composite carbon is formed and hydrothermal reaction with sulfur, the problem of poor conductivity of sulfur/carbon composite positive electrode is solved, and rapid electron transfer and improvement of lithium-sulfur battery performance is achieved.

CN119118125BActive Publication Date: 2025-04-04JIANGSU LONGHU NEW ENERGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411300291.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2025-04-04
Estimated Expiration
2044-09-18

AI Technical Summary

Technical Problem

The existing sulfur/carbon composite cathode has poor electrical conductivity, which is not conducive to the rapid transmission of electrons.

Method used

By crushing the bark of Eucommia ulmoides and treating it at high temperature, carbonization is obtained by carbonizing the porous carbon of Eucommia ulmoides, and activation is carried out using potassium hydroxide. Then, the activated porous carbon is modified using graphene oxide and enhancement modifier to form enhanced composite carbon. Finally, hydrothermal reaction with sublimated sulfur is carried out to fully infiltrate the sulfur to obtain a carbon-sulfur composite, and the residue-based porous carbon electrode material is obtained through pyrrole modification.

Benefits of technology

It improves the conductivity of the electrode material, promotes the rapid transmission of electrons, and improves the comprehensive performance of lithium-sulfur batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119118125B_ABST
    Figure CN119118125B_ABST
Patent Text Reader

Abstract

The invention relates to the field of batteries and is used to solve the problem that the existing sulfur / carbon composite positive electrode has poor conductivity and is not conducive to the rapid transfer of electrons. In particular, it relates to a preparation method of an extraction residue-based porous carbon electrode material. The preparation method uses eucommia bark as a main raw material. The main element composition of the biomass porous carbon material prepared from the eucommia bark includes, in addition to carbon, a small amount of polar elements such as O, H, N, S, etc., so as to improve its adsorption performance and ion exchange performance. The activated eucommia porous carbon has a developed pore structure and a large specific surface area. Then, graphene oxide and an enhanced modifier are used to modify the activated porous carbon, so as to improve the dispersibility and bonding force of the activated porous carbon and enhance its conductivity, thereby improving the rapid transfer of electrons and improving the comprehensive performance of a battery prepared from the residue-based porous carbon electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of batteries, and in particular to a method for preparing an extraction residue-based porous carbon electrode material. Background Art

[0002] In the era of rapid development of electronic information and industrial technology, the preparation of high specific capacity batteries has a great role in promoting the use and promotion of electronic equipment and electric vehicles. The theoretical specific capacity of lithium-sulfur batteries is more than 6 times that of existing ordinary commercial lithium-ion batteries, and the cost is low, so it has great application prospects. In the electrochemical reaction of sulfur and lithium, sulfur has poor conductivity, which is not conducive to the rapid transfer of electrons. Porous carbon materials not only have rich pore structures and good conductivity, but also can be used as sulfur carrier materials. Sulfur can be fixed in the carbon matrix and is conducive to the rapid extraction of sulfur gains and losses. Therefore, in order to increase the electron transfer rate per unit area of ​​battery electrodes and improve the utilization rate of active substances, porous carbon has become the preferred material for preparing sulfur / carbon composite positive electrodes for lithium-sulfur batteries.

[0003] How to improve the poor conductivity of the existing sulfur / carbon composite positive electrode, which is not conducive to the rapid transfer of electrons, is the key to the present invention. Therefore, a preparation method of an extraction residue-based porous carbon electrode material is urgently needed to solve the above problems. Summary of the invention

[0004] In order to overcome the above technical problems, the purpose of the present invention is to provide a method for preparing an extraction residue-based porous carbon electrode material, which solves the problem that the existing sulfur / carbon composite positive electrode has poor conductivity and is not conducive to the rapid transfer of electrons.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] A method for preparing an extraction residue-based porous carbon electrode material comprises the following steps:

[0007] Step 1: Select clean Eucommia bark, place it in a grinder and grind it, place the crushed product in a high-temperature tubular furnace, heat it to 300-320°C in a nitrogen atmosphere and keep it warm for 30-50min, control the heating rate to 3-4°C / min, then heat it to 800-820°C and keep it warm for 2-3h, control the heating rate to 5-7°C / min, then cool it to 90-100°C with the furnace, then wash it with hydrochloric acid solution, anhydrous ethanol and distilled water for 3-5 times in sequence, then place it in a vacuum drying oven, and dry it at a temperature of 80-90°C for 12-15h to obtain Eucommia porous carbon;

[0008] Step 2: Add the eucommia porous carbon, potassium hydroxide and deionized water into a three-necked flask equipped with a stirrer, a thermometer and an air guide tube, stir and mix for 30-80 minutes at a temperature of 110-120°C and a stirring rate of 350-450r / min, then place in a vacuum drying oven, dry for 12-15 hours at a temperature of 50-55°C, then wash with hydrochloric acid solution and distilled water 3-5 times in sequence, and then place in a vacuum drying oven again for drying to obtain activated porous carbon;

[0009] Step 3: Add activated porous carbon, graphene oxide and tetrahydrofuran to a three-necked flask equipped with a stirrer and a thermometer, and ultrasonically disperse for 30-40 minutes at a temperature of 20-25°C and an ultrasonic power of 60-80W, then add a reinforcing modifier and N, N-diisopropylethylamine, and stir the reaction for 15-20 hours at a temperature of 3-5°C and a stirring rate of 350-450r / min. After the reaction is completed, the reaction product is rotary evaporated to remove the solvent, and then added to a hydrochloric acid solution for immersion for 30-50 minutes, and then vacuum filtered, and the filter cake is washed with an ethanol solution for 3-5 times, and then placed in a vacuum drying oven, and dried for 5-7 hours at a temperature of 30-35°C to obtain an enhanced composite carbon;

[0010] Step 4: Grind the reinforced composite carbon and sublimated sulfur in a mortar for 30-50 minutes, add them into a hydrothermal reactor, react for 12-15 hours at a temperature of 155-158°C, allow the sulfur to fully infiltrate the reinforced composite carbon, and then cool to room temperature to obtain a carbon-sulfur composite;

[0011] Step 5: Add the carbon-sulfur complex, deionized water and hexadecyltrimethylammonium bromide to a three-necked flask equipped with a stirrer, a thermometer and a constant pressure dropping funnel, and ultrasonically disperse for 30-40 minutes at a temperature of 20-25°C and an ultrasonic frequency of 45-55kHz, then add the pyrrole solution, stir and react for 15-20 minutes at a temperature of 3-5°C and a stirring rate of 350-450r / min, then add the ammonium persulfate solution dropwise while stirring, and control the dropping rate to 1-2 drops / s. After the dropwise addition is completed, continue to stir and react for 8-10 hours. After the reaction is completed, vacuum filter the reaction product, wash the filter cake with distilled water 3-5 times, and then place it in a vacuum drying oven and dry it at a temperature of 55-60°C for 10-12 hours to obtain the extraction residue-based porous carbon electrode material;

[0012] The reaction process is as follows:

[0013]

[0014] As a further solution of the present invention: the molar concentration of the hydrochloric acid solution in step 1 is 0.1-0.5 mol / L.

[0015] As a further solution of the present invention: the usage ratio of the eucommia porous carbon, potassium hydroxide and deionized water in step 2 is 8-10g:2g:80-100mL, and the molar concentration of the hydrochloric acid solution is 0.1-0.5mol / L.

[0016] As a further scheme of the present invention: the dosage ratio of the activated porous carbon, graphene oxide, tetrahydrofuran, reinforcing modifier and N,N-diisopropylethylamine in step three is 10g: 0.5-2.5g: 200-300mL: 0.8-2.4g: 0.05-0.08g, the molar concentration of the hydrochloric acid solution is 1-1.5mol / L, and the volume fraction of the ethanol solution is 70-80%.

[0017] As a further solution of the present invention: the mass ratio of the reinforced composite carbon to the sublimated sulfur in step 4 is 4:6.

[0018] As a further scheme of the present invention: the amount ratio of the carbon-sulfur complex, deionized water, hexadecyltrimethylammonium bromide, pyrrole solution and ammonium persulfate solution in step five is 1g:100-120mL:0.05-0.08g:40-50mL:100-120mL, the pyrrole solution is a mixture of pyrrole and anhydrous ethanol in a volume ratio of 1-10:50, the ammonium persulfate solution is a solution formed by dissolving ammonium persulfate in a hydrochloric acid solution in a dosage ratio of 0.22-0.36g:50mL, and the molar concentration of the hydrochloric acid solution is 1mol / L.

[0019] As a further solution of the present invention: the reinforcing modifier is prepared by the following steps:

[0020] A1: 2-cyanothiophene and chloroform were added to a three-necked flask equipped with a stirrer, a thermometer, an air guide tube and a constant pressure dropping funnel, and nitrogen was introduced for protection. Trifluoromethanesulfonic acid was added dropwise while stirring at a temperature of 0-3°C and a stirring rate of 350-450 r / min, and the dropping rate was controlled to be 1-2 drops / s. After the addition was completed, the reaction was continued with stirring for 1-2 hours, and then the temperature was raised to 25-35°C while stirring, and the heating rate was controlled to be 1-2°C / min. Then, the reaction was stirred at a constant temperature for 15-20 hours. After the reaction was completed, the reaction product was added to an ammonia solution, and then vacuum filtered. The filter cake was recrystallized with a mixed solvent to obtain intermediate 1;

[0021] The reaction process is as follows:

[0022]

[0023] A2: Add intermediate 1 and chloroform to a three-necked flask equipped with a stirrer, a thermometer and a constant pressure dropping funnel, add liquid bromine solution dropwise while stirring at a temperature of 10-15°C and a stirring rate of 350-450r / min, and control the dropping rate to 1-2 drops / s. After the addition is completed, continue to stir and react for 1-2 hours, then heat to 25-35°C while stirring, control the heating rate to 1-2°C / min, and then stir and react at a constant temperature for 15-20 hours, then add N-bromosuccinimide and continue to stir and react for 2-3 hours. After the reaction, wash the reaction product with saturated sodium bisulfite solution and saturated sodium carbonate solution for 3-5 times in sequence, then let it stand for stratification, and rotary evaporate the organic phase to remove the solvent to obtain intermediate 2;

[0024] The reaction process is as follows:

[0025]

[0026] A3: Pyrrole and anhydrous ether are added to a three-necked flask equipped with a stirrer, a thermometer and a gas duct, and nitrogen is introduced for protection. The reaction is stirred for 15-25 minutes at a temperature of 20-25°C and a stirring rate of 350-450r / min. Potassium tert-butoxide and intermediate 2 are then added and the stirring reaction is continued for 10-15 minutes. The temperature is then raised to 45-50°C and the stirring reaction is continued for 8-10 hours. After the reaction is completed, the reaction product is added to ice water, and then allowed to stand for stratification. The organic phase is rotary evaporated to remove the solvent, and then eluted with an eluent to obtain an enhanced modifier.

[0027] The reaction process is as follows:

[0028]

[0029] As a further scheme of the present invention: the dosage ratio of the 2-cyanothiophene, chloroform and trifluoromethanesulfonic acid in step A1 is 0.1 mol:120-150 mL:0.2-0.25 mol, the mass fraction of the ammonia solution is 5-8%, and the mixed solvent is a mixture of ethyl acetate and petroleum ether in a volume ratio of 1:8-10.

[0030] As a further scheme of the present invention: the usage ratio of the intermediate 1, chloroform, liquid bromine solution and N-bromosuccinimide in step A2 is 0.1 mol:100-120 mL:100-120 mL:0.22-0.25 mol, and the liquid bromine solution is a mixture of liquid bromine and chloroform in a volume ratio of 1.5-2.5:10.

[0031] As a further scheme of the present invention: the usage ratio of the pyrrole, anhydrous ether, potassium tert-butoxide and intermediate 2 in step A3 is 12-20 mmol: 30-40 mL: 15-20 mmol: 10 mmol, and the eluent is a mixture of ethyl acetate and petroleum ether in a volume ratio of 3-5:10.

[0032] Beneficial effects of the present invention:

[0033] The invention discloses a method for preparing an extraction residue-based porous carbon electrode material, which comprises the following steps: crushing eucommia bark and subjecting it to high-temperature treatment to obtain eucommia porous carbon after carbonization, then activating the eucommia porous carbon with potassium hydroxide to obtain activated porous carbon, then modifying the activated porous carbon with graphene oxide and an enhancement modifier to obtain enhanced composite carbon, reacting the enhanced composite carbon with sublimated sulfur to allow sulfur to fully infiltrate the enhanced composite carbon to obtain a carbon-sulfur composite, and modifying the carbon-sulfur composite with pyrrole to obtain the extraction residue-based porous carbon electrode material; the preparation method uses eucommia bark as the main raw material, and eucommia bark is a biomass material, which is not only rich in raw materials, but also has a large amount of C, O, H, N and S elements, so the main element composition of the biomass porous carbon material made from Eucommia bark, in addition to carbon, also contains a small amount of polar elements such as O, H, N, S, and these in-situ polar elements can be combined with carbon elements in the form of chemical bonds to form various polar functional groups, thereby improving its adsorption performance and ion exchange performance. The activated Eucommia porous carbon has a developed pore structure and a large specific surface area. Then, the activated porous carbon is modified using graphene oxide and an enhanced modifier, thereby improving the dispersibility and binding force of the activated porous carbon and enhancing its electrical conductivity, thereby improving the rapid transfer of electrons and improving the comprehensive performance of batteries made from residue-based porous carbon electrode materials.

[0034] In the process of preparing the residue-based porous carbon electrode material, an enhanced modifier is first prepared. First, 2-cyanothiophene is used to react to generate intermediate 1, and then liquid bromine is used to brominate intermediate 1, and bromine atoms are introduced into intermediate 1 to obtain intermediate 2. Then, the bromine atoms on intermediate 2 react with the secondary amino group on pyrrole to undergo nucleophilic substitution reaction, and a pyrrole ring is introduced to obtain an enhanced modifier. Bromine atoms, pyrrole rings, and thiophene rings exist on the enhanced modifier. When the enhanced modifier modifies the activated porous carbon and graphene oxide, the bromine atoms react with the hydrogen-based carboxyl groups on the activated porous carbon and graphene oxide to undergo nucleophilic substitution reaction, thereby enhancing The dispersion of activated porous carbon and graphene oxide can be avoided to agglomerate, and at the same time, the activated porous carbon and graphene oxide can be connected to each other in the form of chemical bonds, thereby increasing the density of the residue-based porous carbon electrode material and improving its mechanical properties. Pyrrole is then used to modify it, and pyrrole is polymerized with the pyrrole ring on the reinforcing modifier to wrap the carbon-sulfur complex, further improving its dispersion. At the same time, the formed polymer molecular chain contains a large number of pyrrole rings and thiophene rings, which can give it good conductive properties. Therefore, the graphene oxide and the reinforcing modifier give the residue-based porous carbon electrode material excellent electrochemical properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] The present invention will be further described below in conjunction with the accompanying drawings.

[0036] Figure 1 It is the constant current charge and discharge curve of the positive electrode sheet corresponding to Comparative Example 1 of the present invention at a rate of 0.1C;

[0037] Figure 2 It is the constant current charge and discharge curve of the positive electrode sheet corresponding to Example 4 of the present invention at a rate of 0.1C;

[0038] Figure 3 is the cyclic voltammetry test curve of the positive electrode sheet corresponding to Comparative Example 1 of the present invention;

[0039] Figure 4 This is the cyclic voltammetry test curve of the positive electrode sheet corresponding to Example 4 of the present invention. DETAILED DESCRIPTION

[0040] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0041] Embodiment 1:

[0042] This embodiment is a method for preparing a reinforcing modifier, comprising the following steps:

[0043] A1: 0.1 mol 2-cyanothiophene and 120 mL chloroform were added to a three-necked flask equipped with a stirrer, a thermometer, an air guide tube and a constant pressure dropping funnel, and nitrogen was introduced for protection. 0.2 mol trifluoromethanesulfonic acid was added dropwise while stirring at a temperature of 0°C and a stirring rate of 350 r / min, and the dropping rate was controlled to be 1 drop / s. After the dropwise addition was completed, the reaction was continued to stir for 1 hour, and then the temperature was raised to 25°C while stirring, and the heating rate was controlled to be 1°C / min. Then, the reaction was stirred at a constant temperature for 15 hours. After the reaction was completed, the reaction product was added to a 5% ammonia aqueous solution by mass, and then vacuum filtered. The filter cake was recrystallized with a mixed solvent of ethyl acetate and petroleum ether in a volume ratio of 1:8 to obtain intermediate 1;

[0044] A2: 0.1 mol intermediate 1 and 100 mL chloroform were added to a three-necked flask equipped with a stirrer, a thermometer and a constant pressure dropping funnel. 100 mL of a liquid bromine solution prepared by mixing bromine and chloroform in a volume ratio of 1.5:10 was added dropwise while stirring at a temperature of 10°C and a stirring rate of 350 r / min. The dropping rate was controlled to be 1 drop / s. After the addition was completed, the reaction was continued with stirring for 1 hour. The temperature was then raised to 25°C while stirring. The heating rate was controlled to be 1°C / min. The reaction was continued with stirring at a constant temperature for 15 hours. 0.22 mol N-bromosuccinimide was then added and the reaction was continued with stirring for 2 hours. After the reaction was completed, the reaction product was washed three times with a saturated sodium bisulfite solution and a saturated sodium carbonate solution in sequence. The mixture was allowed to stand for stratification. The organic phase was rotary evaporated to remove the solvent to obtain intermediate 2.

[0045] A3: 12 mmol pyrrole and 30 mL anhydrous ether were added to a three-necked flask equipped with a stirrer, a thermometer and a gas duct, and nitrogen was introduced for protection. The mixture was stirred for 15 min at a temperature of 20°C and a stirring rate of 350 r / min. Then, 15 mmol potassium tert-butoxide and 10 mmol intermediate 2 were added and the stirring reaction was continued for 10 min. Then, the mixture was heated to 45°C and the stirring reaction was continued for 8 h. After the reaction, the reaction product was added to ice water, and then allowed to stand for stratification. The organic phase was rotary evaporated to remove the solvent, and then eluted with an eluent prepared by mixing ethyl acetate and petroleum ether in a volume ratio of 3:10 to obtain an enhanced modifier.

[0046] Embodiment 2:

[0047] This embodiment is a method for preparing a reinforcing modifier, comprising the following steps:

[0048] A1: 0.1 mol 2-cyanothiophene and 150 mL chloroform were added to a three-necked flask equipped with a stirrer, a thermometer, an air guide tube and a constant pressure dropping funnel, and nitrogen was introduced for protection. 0.25 mol trifluoromethanesulfonic acid was added dropwise while stirring at a temperature of 3°C and a stirring rate of 450 r / min, and the dropping rate was controlled to be 2 drops / s. After the addition was completed, the reaction was continued to stir for 2 hours, and then the temperature was raised to 35°C while stirring, and the heating rate was controlled to be 2°C / min. Then, the reaction was stirred at a constant temperature for 20 hours. After the reaction was completed, the reaction product was added to an 8% ammonia aqueous solution by mass, and then vacuum filtered. The filter cake was recrystallized with a mixed solvent of ethyl acetate and petroleum ether in a volume ratio of 1:10 to obtain intermediate 1;

[0049] A2: 0.1 mol intermediate 1 and 120 mL chloroform were added to a three-necked flask equipped with a stirrer, a thermometer and a constant pressure dropping funnel. 120 mL of a liquid bromine solution prepared by mixing bromine and chloroform in a volume ratio of 2.5:10 was added dropwise while stirring at a temperature of 15°C and a stirring rate of 450 r / min. The dropping rate was controlled to be 2 drops / s. After the addition was completed, the reaction was continued with stirring for 2 h. The temperature was then raised to 35°C while stirring. The heating rate was controlled to be 2°C / min. The reaction was continued with stirring at a constant temperature for 20 h. 0.25 mol N-bromosuccinimide was then added and the reaction was continued with stirring for 3 h. After the reaction was completed, the reaction product was washed 5 times with a saturated sodium bisulfite solution and a saturated sodium carbonate solution in sequence. The mixture was then allowed to stand for stratification. The organic phase was rotary evaporated to remove the solvent to obtain intermediate 2.

[0050] A3: 20 mmol pyrrole and 40 mL anhydrous ether were added to a three-necked flask equipped with a stirrer, a thermometer and a gas guide tube, and nitrogen was introduced for protection. The mixture was stirred for 25 min at a temperature of 25°C and a stirring rate of 450 r / min. Then, 20 mmol potassium tert-butoxide and 10 mmol intermediate 2 were added and the stirring reaction was continued for 15 min. Then, the mixture was heated to 50°C and the stirring reaction was continued for 10 h. After the reaction, the reaction product was added to ice water, and then allowed to stand for stratification. The organic phase was rotary evaporated to remove the solvent, and then eluted with an eluent prepared by mixing ethyl acetate and petroleum ether in a volume ratio of 5:10 to obtain an enhanced modifier.

[0051] Embodiment 3:

[0052] This embodiment is a method for preparing an extraction residue-based porous carbon electrode material, comprising the following steps:

[0053] Step 1: Select clean Eucommia bark, place it in a grinder and grind it, place the crushed product in a high-temperature tubular furnace, heat it to 300°C under a nitrogen atmosphere and keep it warm for 30 minutes, control the heating rate to 3°C / min, then heat it to 800°C and keep it warm for 2 hours, control the heating rate to 5°C / min, then cool it to 90°C with the furnace, then wash it with 0.1 mol / L hydrochloric acid solution, anhydrous ethanol and distilled water for 3 times, then place it in a vacuum drying oven, and dry it at 80°C for 12 hours to obtain Eucommia porous carbon;

[0054] Step 2: 8 g of Eucommia ulmoides porous carbon, 2 g of potassium hydroxide and 80 mL of deionized water were added to a three-necked flask equipped with a stirrer, a thermometer and an air guide tube, stirred and mixed for 30 min at a temperature of 110 ° C and a stirring rate of 350 r / min, then placed in a vacuum drying oven, dried at a temperature of 50 ° C for 12 h, and then washed three times with a hydrochloric acid solution with a molar concentration of 0.1 mol / L and distilled water, and then placed in a vacuum drying oven again for drying to obtain activated porous carbon;

[0055] Step 3: Add 10g activated porous carbon, 0.5g graphene oxide and 200mL tetrahydrofuran to a three-necked flask equipped with a stirrer and a thermometer, and ultrasonically disperse for 30min at a temperature of 20°C and an ultrasonic power of 60W, then add 0.8g of the reinforcing modifier from Example 1 and 0.05g N, N-diisopropylethylamine, and stir the reaction for 15h at a temperature of 3°C and a stirring rate of 350r / min. After the reaction, the reaction product is rotary evaporated to remove the solvent, and then added to a hydrochloric acid solution with a molar concentration of 1mol / L for immersion for 30min, and then vacuum filtered, and the filter cake is washed 3 times with an ethanol solution with a volume fraction of 70%, and then placed in a vacuum drying oven and dried at a temperature of 30°C for 5h to obtain an enhanced composite carbon;

[0056] Step 4: Mix the reinforced composite carbon and sublimed sulfur in a mass ratio of 4:6, place in a mortar and grind for 30 minutes, then add to a hydrothermal reactor, react at a temperature of 155°C for 12 hours to allow the sulfur to fully infiltrate the reinforced composite carbon, and then cool to room temperature to obtain a carbon-sulfur composite;

[0057] Step 5: 1g of carbon-sulfur complex, 100mL of deionized water and 0.05g of hexadecyltrimethylammonium bromide are added to a three-necked flask equipped with a stirrer, a thermometer and a constant pressure dropping funnel, and ultrasonically dispersed for 30 minutes at a temperature of 20°C and an ultrasonic frequency of 45kHz, and then 40mL of pyrrole and anhydrous ethanol are added in a volume ratio of 1:50. The pyrrole solution is stirred for 15 minutes at a temperature of 3°C and a stirring rate of 350r / min, and then 100mL of ammonium persulfate is added dropwise while stirring. The ammonium persulfate solution is formed by dissolving 50mL of ammonium persulfate in a molar concentration of 1mol / L hydrochloric acid solution according to a dosage ratio of 0.22g:50mL, and the dropping rate is controlled to be 1 drop / s. After the dropwise addition is completed, the stirring reaction is continued for 8 hours. After the reaction is completed, the reaction product is vacuum filtered, the filter cake is washed 3 times with distilled water, and then placed in a vacuum drying oven and dried at a temperature of 55°C for 10 hours to obtain the extraction residue-based porous carbon electrode material.

[0058] Embodiment 4:

[0059] This embodiment is a method for preparing an extraction residue-based porous carbon electrode material, comprising the following steps:

[0060] Step 1: Select clean Eucommia bark, place it in a grinder and grind it, place the crushed product in a high-temperature tubular furnace, heat it to 320°C in a nitrogen atmosphere and keep it warm for 50 minutes, control the heating rate to 4°C / min, then heat it to 820°C and keep it warm for 3 hours, control the heating rate to 7°C / min, then cool it to 100°C with the furnace, then wash it with 0.5 mol / L hydrochloric acid solution, anhydrous ethanol and distilled water for 5 times, then place it in a vacuum drying oven, and dry it at 90°C for 15 hours to obtain Eucommia porous carbon;

[0061] Step 2: Add 10g of Eucommia ulmoides porous carbon, 2g of potassium hydroxide and 100mL of deionized water into a three-necked flask equipped with a stirrer, a thermometer and an air guide tube, stir and mix for 80min at a temperature of 120°C and a stirring rate of 450r / min, then place in a vacuum drying oven, dry for 15h at a temperature of 55°C, then wash with a hydrochloric acid solution with a molar concentration of 0.5mol / L and distilled water 5 times, and then place in a vacuum drying oven again for drying to obtain activated porous carbon;

[0062] Step 3: Add 10g activated porous carbon, 2.5g graphene oxide and 300mL tetrahydrofuran to a three-necked flask equipped with a stirrer and a thermometer, and ultrasonically disperse for 40min at a temperature of 25°C and an ultrasonic power of 80W, then add 2.4g of the reinforcing modifier from Example 2 and 0.08g N, N-diisopropylethylamine, and stir the reaction for 20h at a temperature of 5°C and a stirring rate of 450r / min. After the reaction, the reaction product is rotary evaporated to remove the solvent, and then added to a hydrochloric acid solution with a molar concentration of 1.5mol / L for immersion for 50min, and then vacuum filtered, and the filter cake is washed 5 times with an ethanol solution with a volume fraction of 80%, and then placed in a vacuum drying oven and dried at a temperature of 35°C for 7h to obtain enhanced composite carbon;

[0063] Step 4: Mix the reinforced composite carbon and sublimed sulfur in a mass ratio of 4:6, place in a mortar and grind for 50 minutes, then add to a hydrothermal reactor, react at a temperature of 158°C for 15 hours to allow the sulfur to fully infiltrate the reinforced composite carbon, and then cool to room temperature to obtain a carbon-sulfur composite;

[0064] Step 5: 1g of carbon-sulfur composite, 120mL of deionized water and 0.08g of hexadecyltrimethylammonium bromide are added to a three-necked flask equipped with a stirrer, a thermometer and a constant pressure dropping funnel, and ultrasonically dispersed for 40min at a temperature of 25°C and an ultrasonic frequency of 55kHz, then 50mL of pyrrole and anhydrous ethanol are added in a volume ratio of 10:50. The pyrrole solution is stirred for 20min at a temperature of 5°C and a stirring rate of 450r / min, and then 120mL of ammonium persulfate is added dropwise while stirring. The ammonium persulfate solution is formed by dissolving 50mL of ammonium persulfate in a molar concentration of 1mol / L hydrochloric acid solution according to a dosage ratio of 0.36g:50mL, and the dropping rate is controlled to be 2 drops / s. After the dropwise addition is completed, the stirring reaction is continued for 10h. After the reaction is completed, the reaction product is vacuum filtered, the filter cake is washed 5 times with distilled water, and then placed in a vacuum drying oven and dried at a temperature of 60°C for 12h to obtain the extraction residue-based porous carbon electrode material.

[0065] Comparative Example 1:

[0066] This comparative example is a method for preparing an extraction residue-based porous carbon electrode material, comprising the following steps:

[0067] Step 1: Select clean Eucommia bark, place it in a grinder and grind it, place the crushed product in a high-temperature tubular furnace, heat it to 320°C in a nitrogen atmosphere and keep it warm for 50 minutes, control the heating rate to 4°C / min, then heat it to 820°C and keep it warm for 3 hours, control the heating rate to 7°C / min, then cool it to 100°C with the furnace, then wash it with 0.5 mol / L hydrochloric acid solution, anhydrous ethanol and distilled water for 5 times, then place it in a vacuum drying oven, and dry it at 90°C for 15 hours to obtain Eucommia porous carbon;

[0068] Step 2: Add 10g of Eucommia ulmoides porous carbon, 2g of potassium hydroxide and 100mL of deionized water into a three-necked flask equipped with a stirrer, a thermometer and an air duct, stir and mix for 80min at a temperature of 120°C and a stirring rate of 450r / min, then place in a vacuum drying oven, dry at a temperature of 55°C for 15h, then wash with a hydrochloric acid solution with a molar concentration of 0.5mol / L and distilled water for 5 times, and then place in a vacuum drying oven again for drying to obtain the extraction residue-based porous carbon electrode material.

[0069] Dissolve polyvinylidene fluoride in N-methylpyrrolidone, then add the extraction residue-based porous carbon electrode material and acetylene black in Example 4 or Comparative Example 1 and stir evenly to form a slurry, and evenly apply the slurry on an aluminum foil, then dry it, and punch it into a circular positive electrode sheet with a diameter of 12 mm, wherein the mass ratio of the extraction residue-based porous carbon electrode material, acetylene black and polyvinylidene fluoride is 7:2:1;

[0070] The circular positive electrode sheets were assembled into LIR 2032 button cells, in which the negative electrode was a lithium sheet, a porous polyethylene membrane was used as a separator, and the electrolyte was a mixed solution of 1 mol / L lithium bistrifluoromethanesulfonyl imide (LiTFSI) in ethylene glycol dimethyl ether (DME) / 1,3-dioxolane (DOL) (volume ratio of 1:1) and 1% LiNO3.

[0071] The performance of the battery made of the extraction residue-based porous carbon electrode material in Example 4 and Comparative Example 1 was tested. The test results of the charge and discharge performance test are as follows: Figure 1-Figure 2 The cyclic voltammetry test results are shown in Figure 3-Figure 4 shown.

[0072] according to Figure 1-Figure 2It can be seen from the corresponding data of the curve that the first discharge specific capacity of the positive electrode sheet corresponding to Comparative Example 1 is 661.08 mA h / g, while the first discharge specific capacity of the positive electrode sheet corresponding to Example 4 is significantly higher, which is 771.54 mAh / g. As the electrochemical reaction proceeds, the capacity of the two electrodes decays. However, compared with the positive electrode sheet corresponding to Comparative Example 1, the capacity decay of the positive electrode sheet corresponding to Example 4 is significantly slower, and the electrode polarization phenomenon is improved. After the 20th cycle, the discharge specific capacity of the positive electrode sheet corresponding to Example 4 is maintained at 484.09 mA h / g, and the capacity retention rate is 62.7%, while the discharge specific capacity of the positive electrode sheet corresponding to Comparative Example 1 is 289.13 mA h / g, and the capacity retention rate is only 43.7%.

[0073] according to Figure 3-Figure 4 When the scanning rate is 0.1mV / s, the cyclic voltammetry test curves of the positive electrode sheet corresponding to Example 4 and the positive electrode sheet corresponding to Comparative Example 1 are between 1.0-3.5V, and the CV curves of the two electrodes are similar in shape, but the peak intensities are different. The positive electrode sheet corresponding to Comparative Example 1 has two reduction peaks near 2.2V and 2.0V, and an oxidation peak appears near 2.6V. The curves have good overlap, indicating that the battery has good cycle performance. The two reduction peaks of the positive electrode sheet corresponding to Example 4 appear near 1.9V and 2.2V, and the oxidation peak appears near 2.6V. It can be seen from the figure that the closed area of ​​the CV curve of the positive electrode sheet corresponding to Example 4 is significantly larger than that of the positive electrode sheet corresponding to Comparative Example 1, showing better electrochemical performance.

[0074] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0075] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A method for preparing an extraction residue-based porous carbon electrode material, characterized in that: The following steps are involved: Step 1: crushing the bark of Eucommia ulmoides, placing the crushed product in a high-temperature tube furnace for high-temperature treatment, then cooling it with the furnace and washing it with hydrochloric acid solution, anhydrous ethanol and distilled water in sequence, and then drying it to obtain Eucommia ulmoides porous carbon; Step 2: Add the eucommia porous carbon, potassium hydroxide and deionized water into a three-necked flask and stir to mix, then dry and wash with hydrochloric acid solution and distilled water in sequence, and then dry again to obtain activated porous carbon; Step 3: Add activated porous carbon, graphene oxide and tetrahydrofuran into a three-necked flask for ultrasonic dispersion, then add a reinforcing modifier and N, N-diisopropylethylamine for stirring reaction, after the reaction is completed, rotary evaporate the reaction product, then add it into a hydrochloric acid solution for soaking, then vacuum filter, wash the filter cake with an ethanol solution, and then dry it to obtain a reinforced composite carbon; Step 4: Grind the reinforced composite carbon and sublimated sulfur, add them into a hydrothermal reactor for reaction, and then cool to room temperature to obtain a carbon-sulfur composite; Step 5: Add the carbon-sulfur complex, deionized water and hexadecyltrimethylammonium bromide into a three-necked flask and disperse them by ultrasonic, then add the pyrrole solution and stir to react, then add the ammonium persulfate solution dropwise while stirring, continue stirring to react after the addition is complete, vacuum filter the reaction product after the reaction is completed, wash the filter cake with distilled water, and then dry to obtain the extraction residue-based porous carbon electrode material.

2. The method for preparing an extraction residue-based porous carbon electrode material according to claim 1, characterized in that: The molar concentration of the hydrochloric acid solution in step 1 is 0.1-0.5 mol / L.

3. The method for preparing an extraction residue-based porous carbon electrode material according to claim 1, characterized in that: The usage ratio of the eucommia porous carbon, potassium hydroxide and deionized water in step 2 is 8-10g:2g:80-100mL, and the molar concentration of the hydrochloric acid solution is 0.1-0.5mol / L.

4. The method for preparing an extraction residue-based porous carbon electrode material according to claim 1, characterized in that: The amount ratio of the activated porous carbon, graphene oxide, tetrahydrofuran, reinforcing modifier and N,N-diisopropylethylamine in step three is 10g: 0.5-2.5g: 200-300mL: 0.8-2.4g: 0.05-0.08g, the molar concentration of the hydrochloric acid solution is 1-1.5mol / L, and the volume fraction of the ethanol solution is 70-80%.

5. The method for preparing an extraction residue-based porous carbon electrode material according to claim 1, characterized in that: The mass ratio of the reinforced composite carbon to the sublimated sulfur in step 4 is 4:

6.

6. The method for preparing an extraction residue-based porous carbon electrode material according to claim 1, characterized in that: The amount ratio of the carbon-sulfur complex, deionized water, hexadecyltrimethylammonium bromide, pyrrole solution and ammonium persulfate solution in step 5 is 1g:100-120mL:0.05-0.08g:40-50mL:100-120mL, the pyrrole solution is a mixture of pyrrole and anhydrous ethanol in a volume ratio of 1-10:50, the ammonium persulfate solution is a solution formed by dissolving ammonium persulfate in a hydrochloric acid solution in a dosage ratio of 0.22-0.36g:50mL, and the molar concentration of the hydrochloric acid solution is 1mol / L.

7. The method for preparing an extraction residue-based porous carbon electrode material according to claim 1, characterized in that: The reinforcing modifier is prepared by the following steps: A1: 2-cyanothiophene and chloroform were added to a three-necked flask, and trifluoromethanesulfonic acid was added dropwise while stirring. After the addition was completed, stirring was continued for reaction. After the reaction was completed, the reaction product was added to an aqueous ammonia solution, and then vacuum filtered. The filter cake was recrystallized to obtain intermediate 1; A2: Add intermediate 1 and chloroform into a three-necked flask, add liquid bromine solution dropwise while stirring, continue stirring to react after the addition is complete, then add N-bromosuccinimide and continue stirring to react, after the reaction is complete, wash the reaction product with saturated sodium bisulfite solution and saturated sodium carbonate solution in sequence, then let stand to separate, and rotary evaporate the organic phase to obtain intermediate 2; A3: Pyrrole and anhydrous ether were added into a three-necked flask and stirred for reaction. Potassium tert-butoxide and intermediate 2 were then added and stirred for reaction. After the reaction was completed, the reaction product was added into ice water and allowed to stand for stratification. The organic phase was rotary evaporated and then eluted to obtain an enhanced modifier.

8. The method for preparing an extraction residue-based porous carbon electrode material according to claim 7, characterized in that: The usage ratio of the 2-cyanothiophene, chloroform and trifluoromethanesulfonic acid in step A1 is 0.1 mol: 120-150 mL: 0.2-0.25 mol, and the mass fraction of the ammonia solution is 5-8%.

9. The method for preparing an extraction residue-based porous carbon electrode material according to claim 7, characterized in that: The usage ratio of the intermediate 1, chloroform, liquid bromine solution and N-bromosuccinimide in step A2 is 0.1 mol: 100-120 mL: 100-120 mL: 0.22-0.25 mol, and the liquid bromine solution is a mixture of liquid bromine and chloroform in a volume ratio of 1.5-2.5:

10.

10. The method for preparing an extraction residue-based porous carbon electrode material according to claim 7, characterized in that: The usage ratio of the pyrrole, anhydrous ether, potassium tert-butoxide and intermediate 2 in step A3 is 12-20 mmol: 30-40 mL: 15-20 mmol: 10 mmol.

Citation Information

Patent Citations

  • Method for preparing eucommia ulmoides gum and activated carbon by utilizing eucommia ulmoides

    CN104448344A

  • Method for extracting eucommia ulmoides gum from eucommia ulmoides and preparing active carbon

    CN104495840A